AKTIVITAS ANTIBAKTERI EKSTRAK METANOL DAUN KENITU (Chrysophyllum cainito L.) TERHADAP Salmonella thypi ATCC 422 - Ade Dinaran; Chairul Saleh; Djihan Ryn Pratiwi (PROSIDING SEMINAR KIMIA, 2023)
Kenitu (Chrysophyllum cainito L.) is one of the plants that has the potential to cure fever, diarrhea and inflammation of the respiratory tract. This study aimed to determine the minimum inhibitory concentration value of kenitu leaf methanol extract (Chrysophyllum cainito L.) against Salmonella thypi bacteria ATCC 422. The minimum inhibitory concentration value of kenitu (Chrysophyllum cainito L.) against Salmonella thypi ATCC 422 bacteria was 0.625 %. The presence of antibacterial activity of kenitu leaf methanol extract (Chrysophyllum cainito L.) contains secondary metabolite compounds of alkaloid, phenolic and steroid groups. Keywords: Chrysophyllum cainito L., antibacterial, minimum inhibitory concentration, Salmonella thypi ATCC 422